STUDI SEBARAN KEDALAMAN PIRIT DAN SALINITAS PADA LAHAN PASANG SURUT DI DESA PEMUSIRAN, JAMBI - Bisri, Muhammad Adib; Antony, Dedy; Mastur, Agus Kurniawan; Citra, Riesca Wulanda (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
Marginal lands such as tidal lands used for agriculture face several problems, including shallow pyrite layers, land affected by seawater intrusion (salinity), high soil acidity (low pH) and nutrient-poor soil. The shallow pyrite layers and salinity in Pemusiran Village are major obstacles to agricultural development and have resulted in decreased land productivity. This research aims to determine and analyze the distribution of pyrite layer depth, Soil Electrical Conductivity (EC) and groundwater in Pemusiran Village. This research uses a survey method, where observation points are determined using the grid method. The results of the study showed that the sulfidic material layer (pyrite) of the soil at the research location was dominated by pyrite depth of 50-100 cm, which was included in the potential acid sulfate soil typology (PASS) category, namely PASS-2 with an area of 1,055.32 ha or 45.73% of the total research area. The depth of the pyrite layer at the research location was influenced by the distance from the sea and rivers, land management and the thickness of the peat layer. The soil EC value at the research location ranged from 64-981 μs cm-1 in the very low category. The highest EC value for groundwater was 8,863 μs cm-1 in the poor category and the lowest value was 355 μs cm-1 in the good category. Generally, the highest EC values for soil and groundwater were in coastal areas and were lower in areas far from the coast and rivers.